A Case Study of The Role of Ureter Tracking Reconstruction in Clinical Urology CT Scan Examination of Kidney Stones in the Radiology Installation of RSUD dr. Loekmono Hadi Kudus - Daniya, Tisya Yin; Astari, Fisnandya Meita; Mufida, Widya (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
This study aims to determine the clinical urology CT scan procedure for kidney stones, analyze the justification for employing ureteral tracking reconstruction, and evaluate the ideal slice thickness for achieving accurate diagnostic images. This research employed a descriptive qualitative methodology utilizing a case study technique in the Radiology Department of RSUD (Regional General Hospital) dr. Loekmono Hadi Kudus. The subjects comprised of three radiographers, one radiologist, one referring physician, and three CT scan images of the urology. Data was obtained through observation, interviews, documentation, and literature review. The data were subsequently studied through reduction, presentation, discussion, and conclusion formulation. The examination was conducted without any specific preparation, merely by consuming 500-750 ml of water and refraining from urinating. The patient was placed in a supine position, feet-first, with arms elevated above the head, exposing the area from the xiphoid process to the symphysis pubis. A 5 mm slice thickness was employed for axial imaging, while 1.5 mm was utilized for tracking reconstruction. The ureteral tracking technique offers an extensive visualization of the urinary tract, facilitating in the detection of stones and obstructions. A reduced slice thickness improves image clarity and elucidates anatomical details. The application of a thin slice thickness (≤1.5 mm) is essential for enhancing picture clarity, facilitating in the identification of small, and minimizing interpretative inaccuracies. Consequently, the use of ureteral tracking reconstruction with a thin slice thickness is highly recommended as a standard practice for urological CT scans in kidney stone cases.